2020
DOI: 10.1101/2020.02.16.951780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Structures of Secretory and Dimeric Immunoglobulin A

Abstract: Secretory (S) Immunoglobulin (I) A is the predominant mucosal antibody, which binds pathogens and commensal microbes. SIgA is a polymeric antibody, typically containing two copies of IgA that assemble with one joiningchain (JC) to form dimeric (d) IgA that is bound by the polymeric Ig-receptor ectodomain, called secretory component (SC). Here we report the cryo-electron microscopy structures of murine SIgA and dIgA. Structures reveal two IgAs conjoined through four heavy-chain tailpieces and the JC that togeth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, the structures revealed that the SC undergoes a large conformational rearrangement from a closed, apo state (Stadtmueller et al, 2016), to an open, extended conformation upon polymeric IgA binding. Our structures are highly consistent with two additional reported structures of murine (Kumar Bharathkar et al, 2020) and human sIgA (Wang et al, 2020).…”
Section: Introductionsupporting
confidence: 90%
“…Furthermore, the structures revealed that the SC undergoes a large conformational rearrangement from a closed, apo state (Stadtmueller et al, 2016), to an open, extended conformation upon polymeric IgA binding. Our structures are highly consistent with two additional reported structures of murine (Kumar Bharathkar et al, 2020) and human sIgA (Wang et al, 2020).…”
Section: Introductionsupporting
confidence: 90%
“…Recent structural insights from our research and others have revealed the molecular mechanism of the J chain in promoting IgM and IgA polymerization, as well as its role in the recognition of IgM and IgA by pIgR 30,31,[33][34][35] . In this study and another study 42 , we further demonstrate that the J chain also plays a crucial role in mediating the interaction between the IgM pentamer and CD5L, as well as between systemic IgA and FcRL4.…”
Section: Discussionmentioning
confidence: 81%
“…2b). It is worth noting that this hairpin structure, observable in IgA structures [33][34][35] , was disordered in all previous IgM structures without CD5L. In SRCR2, K173 and R183 interact with E77J and E75J (J chain residues are denoted by subscripts), respectively; whereas V185-T187 pack with N80J-I82J.…”
Section: Cryo-em Structure Of Human Fcμ-j-cd5lmentioning
confidence: 89%
“…PIgR is localized to the basolateral side of epithelial cells and moreover cannot bind secretory IgA, making it unlikely to be involved in IgA feedback signaling to the epithelium. In secretory IgA, the Fc portion of the antibody is partially obscured by the SC 70 , and colon epithelial cells do not express a typical Fc receptor that binds the alpha heavy chain. However, many proteins have reported interactions with IgA, leaving open the possibility of a non-conventional antibody receptor being responsible for such epithelial feedback.…”
Section: Discussionmentioning
confidence: 99%